THEORETICAL FOUNDATIONS OF DEVELOPING COGNITIVE COMPETENCY THROUGH TRILINGUAL SOFTWARE IN MATHEMATICS LESSONS - Saidova Zulfizar Askarovna (Modern American Journals, 2025)
This article presents the theoretical foundations for developing students' cognitive competencies through the use of trilingual software in mathematics lessons. It analyzes the impact of educational software on cognitive development, the opportunities for trilingual (Uzbek, Russian, and English) instruction, and the role of trilingual technologies in fostering thinking, analytical reasoning, and problem-solving skills.
Keywords: Semantic analysis, metacognition, functional context, analytical thinking, didactic function, digital education, software platform, modular learning, QR-coded task, blended learning, divergent thinking, GeoGebra, Desmos, Khan Academy.